IMPLEMENTASI EVALUASI MODEL KUALITAS PROSES DAN OUTPUT PEMBELAJARAN PADA MATA KULIAH MAGANG I - St Jumaeda (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
This research aims to obtain an overview of the implementation of evaluation of process quality models and output quality in Internship learning.I. This research is an evaluative research approach using a model developed by Widoyoko, Which includes two main components, namely: process quality and quality of learning output. The sample in this study was a student of the Islamic Religious Education study program of the Faculty of Tarbiyah Science and Iain Ambon Teacher Training numbering 32 students. Data collection is obtained through document studies, interviews, questionnaires and observations. The data is then classified into very less, less, sufficient, good and excellent categories, based on the standards of assessment evaluation made at each stage of evaluation, and decision making. The findings in the evaluation of the Internship I Learning Program of Islamic Religious Education Faculty of Tarbiyah Science and IAIN Ambon Teacher Training, showed that the quality of the learning program process, including the good category, and the quality of internship learning output I also belonged to the excellent category. Taking into account the previous facts there are several aspects in the evaluation of the quality of the process and the quality of learning output that need to be improved so that internship learning I will be more effective and achieve the competencies that have been planned.Keywords: evaluation of process quality and quality of learning output, internship I